Acts Against Civil Law Versus Acts Against Criminal Law Versus Rechtsvinding HogeRaad / Supreme Judge - Fernando, Youngky (The International Journal of Law Review and State Administration, 2024)
An unlawful act in Dutch is called "onrechmatige daad" and in English, it is called "tort" which means "wrong". The word "tort" developed to mean civil "wrong" that does not result from "default". So it is similar to the meaning of "act against the law" which is called "onrechmatigedaad" in the Dutch legal system. The word "tort" comes from the Latin word "torquere" or "tortus" in French, just as the word "wrong" comes from the French word "wrung" which means "mistake or loss" (injury). The principle and aim of establishing a legal system for "unlawful acts" are to be able to achieve what is said in the Latin proverb, namely Juris praecepta sunt luxe, honestevivere, alterum nonlaedere, suum cuique tribuere (the motto of the law is to live honestly, not harming people). others, and give others their rights). Onrechtmatigedaad (acts against the law) Article 1365 of the Civil Code or Burgerlijk Wetboek-Netherland Article 1401: "Elke onrecthamatigedaad, waardoor aan een ander schade wordt toegebragt, stelt dengene door wiens shuld die schade veroorzaakt is in de verpligting om dezelve te vergoeden ”. Soebekti and Tjitrosudibio translate it: "Every act against the law, which causes loss to another person, requires the person whose fault it was to cause the loss, to compensate for the loss." Later, after January 31, 1919, one element was added to "Unlawful Acts", namely, the prohibition of violating other people's rights and contradicting morality and propriety in living in society, nation, state vs human rights.